Multiomics analysis revealed miRNAs as potential regulators of the immune response in Carassius auratus gills to Aeromonas hydrophila infection - Huo, Jiaxin; Hu, Xiucai; Bai, Jie; Lv, Aijun (Frontiers in Immunology, 2023)
The gill of fish is an important immune organ for pathogen defense, but its microRNA (miRNA) expression and regulatory mechanism remain unclear. In this study, we report on the histopathological and immunohistochemical features of the gills of the crucian carp Carassius auratus challenged with Aeromonas hydrophila. Small RNA libraries of the gills were constructed and sequenced on the Illumina HiSeq 2000 platform. A total of 1,165 differentially expressed miRNAs (DEMs) were identified in gills, of which 539 known and 7 unknown DEMs were significantly screened (p < 0.05). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses revealed that the potential target genes/proteins were primarily involved in 33 immune-related pathways, in which the inflammatory responses were focused on the Toll-like receptor (TLR), mitogen-activated protein kinase (MAPK), and nuclear factor kappa B (NF-κB) signaling pathways. Moreover, the expression levels of 14 key miRNAs (e.g., miR-10, miR-17, miR-26a, miR-144, miR-145, and miR-146a) and their target genes (e.g., TNFα, TLR4, NF-κB, TAB1, PI3K, and IRAK1) were verified. In addition, the protein levels based on isobaric tags for relative and absolute quantification (iTRAQ) were significantly associated with the results of the quantitative real-time PCR (qRT-PCR) analysis (p < 0.01). miR-17/pre-miR-17 were identified in the regulation expression of the NF-κB target gene, and the phylogenetic tree analysis showed that the pre-miR-17 of C. auratus with the closest similarity to the zebrafish Danio rerio is highly conserved in teleosts. This is the first report of the multi-omics analysis of the miRNAs and proteins in the gills of C. auratus infected with A. hydrophila, thus enriching knowledge on the regulation mechanism of the local immune response in Cyprinidae fish.